A facile synthesis of novel endo-selective polycyclic spiropyrrolidine oxindoles via 1, 3-dipolar cycloaddition of α, γ-dialkylallenoate esters. Issue 16 (19th April 2017) - Wang, Yingwei; Chen, Yuanwei
Graphical abstract: Highlights: A three-component reaction of α, γ-dialkylallenoate esters, isatin derivatives with amino acids. High yields (up to 92%) and diastereoselectivities (up to >20:1). Two contiguous quaternary stereogenic centers are formed in target products. A stereochemical model was proposed to rationalize the observed stereoselectivity. Abstract: Novel polycyclic spiropyrrolidine oxindoles that bear two vicinal quaternary centers and an exocyclic CC double bond have been synthesized by a three-component reaction involving α, γ-dialkylallenoate esters, isatin derivatives and amino acids, by way of an endo -selective 1, 3-dipolar cycloaddition. These reactions proceed in high yields and diastereoselectivities. The structures and relative stereochemistry of products were confirmed by NMR, HRMS and X-ray crystallography.